Highly stable hierarchical porous nanosheet composite phase change materials for thermal energy storage. (25th December 2019) - Zuo, Xiaochao; Yan, Zhaoli; Hou, Kai; Yang, Huaming; Xi, Yunfei
Graphical abstract: Highlights: Hierarchical porous nanosheets (HPNTs) were synthesized from kaolinite. The HPNTs were modified by grafting with (3-aminopropyl)triethoxysilane (APTES) APTES-modified HPNT (NH2 -HPNT) was used a substrate for phase-change materials. Novel stearic acid-based (SA-based) phase-change materials were prepared. NH2 -HPNT is a promising supporting material for thermal energy-storage applications. Abstract: Thermal energy storage is considered as an effective strategy for improving energy efficiency, and phase change materials (PCMs) are promising in that regard. However, the leakage in the melting process and low thermal conductivity of phase change materials are a big challenge for their practical application. Herein we prepared an amino-functional hierarchical porous nanosheet (NH2 -HPNT) by the template-free structural reorganisation of natural clay mineral (kaolinite) and subsequent modification with (3-aminopropyl) triethoxysilane (APTES). NH2 -HPNT was hybridized with stearic acid (SA) to produce novel form-stable composite phase change material (PCM). The effect of the NH2 -HPNT microstructure on the thermal properties of the composite PCM was investigated. The samples were characterized by X-ray diffraction (XRD), Fourier-transform infrared (FTIR) spectroscopy, differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and differential thermogravimetry (DTG). After serious leakage testing, the maximum amount of SA loaded onto NH2 -HPNT without leakage was determined to be 63.5 wt%. NH2 -HPNT/SA composite PCM melts at 68.3 °C with a phase change enthalpy of 118.6 J/g, and solidifies at 63.7 °C with that of 111.8 J/g. The as-prepared composite PCM is thermally stable. In comparison with SA, the thermal conductivity of NH2 -HPNT/SA increase by up to 60%. Additionally, thermal cycling experiments showed that NH2 -HPNT/SA is significantly more reliable than HPNT/SA after 200 heating cycles. The mechanism responsible for improving the thermal properties of the composite PCMs is proposed. The results indicate that NH2 -HPNT could be a promising supporting material for PCMs in thermal energy storage applications.